Telemedicine: Between Opportunities, Expectations, and Challenges in Health Development in Remote Areas of Indonesia - Cut Khairunnisa; Al Muqsith; Nur Fardian; Maulina Debbyousha; Shabrina Shabrina (Lembaga Pusat Studi Sosial dan Humaniora [LPS2H], 2025)
Current technological advancements have helped Indonesian society access healthcare services more easily than before. Telemedicine emerges as a crucial innovation to implement, offering a viable solution to bridge geographical gaps by enabling remote consultations and medical services. The purpose of this study is to identify Indonesia's opportunities, expectations, and challenges in providing healthcare services by utilizing telemedicine. This study is a literature review using a narrative descriptive approach. Data was collected through online searches from various sources, including dissertations, theses, scientific publications, and e-books. The analysis results revealed that the utilization of digital technology in providing healthcare services to the community offers significant opportunities to improve the efficiency and convenience of medical services, especially in remote areas. The presence of telemedicine also offers new hope to the community. However, the implementation of telemedicine still faces various challenges and obstacles, including legal regulations, digital infrastructure, technological literacy, and public trust in digital-based healthcare services.